PARE0007 PATIENT AND PUBLIC INVOLVEMENT IN CLINICAL TRIAL DESIGN. (2nd June 2020) - De Souza, S.; Williams, R.; Johansson, E.; Zabalan, C.; Esterine, T.; Bakkers, M.; Roth, W.; MC Carthy, N.; Blake, M.; Karlfeldt, S.; Johannesson, M.; Raza, K.
Abstract : Background: Patient and public involvement (PPI) is gaining increasing recognition as important in ensuring research is relevant and acceptable to participants. Rheuma Tolerance for Cure (RTCure) is a 5 year international collaboration between academia and industry; focusing on earlier detection and prevention of rheumatoid arthritis (RA) through the use of immune-tolerising treatments. Objectives: To bring lived experience and insight into scientific discussions; and to evolve collaboration between lay representatives and academia/industry. Methods: 9 Patient Research Partners (PRPs) from 5 European countries were recruited via the EULAR PARE Network and institutions within the RTCure Consortium (8 PRPs with RA and 1 'at risk'). They were asked to enter into a legal agreement with the Consortium. PRPs participated in teleconferences (TCs) and were invited to attend face-to-face (F2F) meetings at least annually. Requests for input/feedback were sent from researchers to PRPs via the project's Patient Engagement Expert [SK]. Results: PRP involvement has given researchers and industry partners a new perspective on patient priorities, and focused thought on the ethics of recruitment for and participation in clinical trials of people 'at risk' of developing RA. PRPs have helped define the target populations, given their thoughts on what types of treatments are acceptable to people 'at risk' and have aided the development of a survey (sent to EULAR PARE members) regarding the use of animal models in biomedical research. Positive informal feedback has been received from researchers and industry regarding the contribution of PRPs to the ongoing project (formal evaluation of PPI in RTCure will be carried out in 2020 and at the project end in 2022). Challenges: Legal agreements - Many PRPs refused to sign the Consortium's complex PRP Agreement; feeling it unnecessary, incomprehensible and inequitable. After extensive consultation with various parties (including EULAR and the Innovative Medicines Initiative) no similar contract was found. Views for its requirement even varied between legal experts. After 2 years of intense discussion, a simple non-disclosure agreement was agreed upon. Ideally any contract, if required, should be approved prior to project onset. Meeting logistics - Other improvements identified were to locate the meeting venue and accommodation on the same site to minimise travel, and to make it easier for PRPs to take breaks when required. This also facilitates informal discussions and patient inclusivity. We now have agreed a policy to fund PRPs extra nights before and after meetings, and to bring a carer if needed. Enabling understanding – Future annual meetings will start with a F2F meeting between PRPs and Work Package Leads. Researchers will be encouraged to start presentations with a summary slide in lay language. Additionally, an RTCure Glossary is in development. Enabling participation – SK will provide monthly project updates and PRP TCs will be held in the evening (as some PRPs remain employed). PRPs will be invited to all project TCs and F2F meetings. Recruitment is underway to increase the number of 'at risk' PRPs as their viewpoint is vital to this study. Conclusion: Currently PPI in RTCure is an ongoing mutual learning process. Universal guidance regarding what types of contracts are needed for PPI would be useful. Communication, trust and fruitful discussions have evolved through F2F meetings (both formal and informal) between PRPs, academia and industry. It is important that all parties can be open with each other in order to make PPI more meaningful. Acknowledgments: This work has received support from the EU/EFPIA Innovative Medicines Initiative 2 Joint Undertaking RTCure grant number 777357. Disclosure of Interests: Savia de Souza: None declared, Ruth Williams: None declared, Eva Johansson: None declared, Codruta Zabalan: None declared, Tom Esterine: None declared, Margôt Bakkers: None declared, Wolfgang Roth: None declared, Neil Mc Carthy: None declared, Meryll Blake: None declared, Susanne Karlfeldt: None declared, Martina Johannesson: None declared, Karim Raza Grant/research support from: KR has received research funding from AbbVie and Pfizer, Consultant of: KR has received honoraria and/or consultancy fees from AbbVie, Sanofi, Lilly, Bristol-Myers Squibb, UCB, Pfizer, Janssen and Roche Chugai, Speakers bureau: KR has received honoraria and/or consultancy fees from AbbVie, Sanofi, Lilly, Bristol-Myers Squibb, UCB, Pfizer, Janssen and Roche Chugai